Optical properties of InGaAs/GaAs quantum wells with different distance from Si-delta-doping layer - Motyka, Marcin; Sęk, Grzegorz; Andrzejewski, Janusz; Kudrawiec, Robert; Misiewicz, Jan; Ściana, Beata; Radziewicz, Damian; Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In0.22Ga0.78As/GaAs single quantum wells with different distance from a delta doped layer have been investigated by using contactless electroreflectance (CER) spectroscopy. The oscillator strength of optical transitions and the value of the built-in electric field have been determined from CER spectra. Obtained results have been compared with theoretical calculations preformed in the framework of the effective mass approximation. In order to accurately find the wavefunctions of electrons and holes confined in the quantum well embedded in the built-in electric field, the time-dependent Schrödinger equation has been solved.
Optica Applicata, Vol. 35, 2005, nr 3, s. 471-477
Keywords: optyka; quantum well; contactless electroreflectance; built-in electric field; delta-doping